Ответ:
[tex] \frac{ {7}^{11} {7}^{8} }{ {7}^{17} } = {7}^{11 + 8 - 17} = {7}^{2} = 49[/tex]
[tex] \frac{ {( - 2)}^{4} {( - 2)}^{8} }{ {( - 2)}^{9} } = {( - 2)}^{4 + 8 - 9} = {( - 2)}^{3} = - 8[/tex]
[tex] \frac{ {0.3}^{9} {0.3}^{4} }{ {0.3}^{5} {0.3}^{6} } = {0.3}^{9 + 4 - 5 - 6} = {0.3}^{2} = 0.09[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex] \frac{ {7}^{11} {7}^{8} }{ {7}^{17} } = {7}^{11 + 8 - 17} = {7}^{2} = 49[/tex]
[tex] \frac{ {( - 2)}^{4} {( - 2)}^{8} }{ {( - 2)}^{9} } = {( - 2)}^{4 + 8 - 9} = {( - 2)}^{3} = - 8[/tex]
[tex] \frac{ {0.3}^{9} {0.3}^{4} }{ {0.3}^{5} {0.3}^{6} } = {0.3}^{9 + 4 - 5 - 6} = {0.3}^{2} = 0.09[/tex]